(untitled) (Journal of the College of Basic Education, 2022)
The Almighty said: ((He) who created from water a human being, then He made him a lineage and a marriage, and your Lord is powerful ()(). Purely social. And the moral benefit is referred to by Ibn Inaba, saying: ((In the knowledge of lineage impulsive to the honorable morals, as it contains a disdain for vice faculties, so when a person knows in his origin honor and in the return of solidity and in his desire is good and nothing less than that he considers himself a danger in his connection Attributing to a well-known origin - he disavows dealing with worldly matters and committing vices, frustrated at his reputation for being obsequious and disgraceful.